Analisis Laju Keausan Kampas Rem Campuran Arang Sabut Kelapa Dan Kulit Pisang: Wear Rate Analysis Of Coconut Coir And Banana Peel Charcoal Brake Pads - Satria Yoga Ramadhani; Ratna Monasari; Akbar Anugrah (Universitas Pendidikan Ganesha, 2026)
The effect of the combination of coconut coir charcoal and banana peel charcoal on the wear rate of motorcycle brake pads as an eco-friendly, non-asbestos material is evaluated. The biocomposite brake pads were fabricated using 200-mesh coconut coir and banana peel charcoal fillers with a volume fraction variation of 0–50%, compounded with Fe powder, CaCO₃, and polyester resin as the binding matrix. Wear testing was conducted using a disc brake simulator at a speed of 1800 rpm, a braking pressure of 10 psi, and a test duration of 120 seconds for each specimen. The wear rate was calculated based on the mass difference before and after testing relative to the contact surface area and test duration. The results indicate that an increase in coconut coir charcoal content consistently reduces the wear rate, whereas a higher composition of banana peel charcoal causes faster pad wear. The specimen containing 50% coconut coir charcoal, recording a value of 0.000865 g/mm.sec, provided the best wear resistance among all biocomposite variations, while the original equipment manufacturer (OEM) brake pads maintained the lowest wear value as the reference standard. These findings confirm the potential of coconut coir charcoal as the primary reinforcement for polyester resin-based brake pad composites.